Characterization of CO1 and 18S rDNA genes from Indonesian native ornamental shrimp Caridina boehmei cultured in Jakarta - Romadhona, Ekky Ilham; Megawati, Novi; Widantara, Handang; Sutanti, Sutanti; Rahman Ardiansyah, Arif; Mariya Dewi, Kiki; Fitri Larassagita, Annisa; Firman, Aditia; Risky, Moh; Rahmat, Rahmat; Ayub, Ayub (Indonesian Society of Scientific Aquaculture (ISSA), 2024)
Caridina boehmei is an ornamental shrimp native to Sulawesi that has been successfully cultured and marketed in Indonesia. However, molecular information about this shrimp is not yet available. This study aimed to characterize cytochrome c oxidase subunit I (CO1) and small subunit ribosomal RNA (18S rDNA) genes. Shrimp samples were extracted, and DNA was amplified using CO1 and 18S rDNA primers. The sequencing results were then analyzed by the neighbor-joining method. The 654 bp partial coding sequence (cds) of the CO1 and 380 bp partial cds of 18S rDNA have been successfully amplified from genomic DNA. The CO1 sequencing produced fragments consisting of 25.84% adenine, 20.95% cytosine, 19.11% guanine, and 34.10% thymine. The 18S rDNA sequencing produced fragments consisting of 24.47% adenine, 26.05% cytosine, 28.16% guanine, and 21.32% thymine. Phylogenetic analysis based on the CO1 gene revealed that C. boehmei was grouped with C. variabilis (MK190014), C. brachydactyla (MK190011), and Caridina sp. (MK190012). Phylogenetic analysis based on the 18S rDNA gene revealed that C. boehmei was identical to Caridina sp. Suphan Buri-1 MF622000, C. serratirostris KP725708, C. multidentata JF346236, C. formosae GQ131924, and Caridina sp. Suphan Buri-2 MF622001. The lowest-highest pairwise distance based on CO1 and 18S rDNA was consecutively 0.0017-0.2247 (0.17-22.47%) and 0.0000-0.1218 (0-12.18%). Keywords: 18S rDNA, Caridina boehmei, CO1, DNA barcoding, ornamental shrimp ABSTRAK Caridina boehmei merupakan udang hias asli Sulawesi yang telah berhasil dibudidayakan dan dipasarkan di Indonesia. Kendati demikian, informasi molekuler mengenai udang ini belum tersedia. Tujuan penelitian ini yaitu melakukan karakterisasi menggunakan gen sitokrom c oksidase subunit I (CO1) dan RNA ribosomal subunit kecil (18S rDNA). Sampel udang diekstraksi kemudian DNA diamplifikasi dengan menggunakan primer CO1 dan 18S rDNA. Hasil sekuensing kemudian dianalisis dengan metode neighbor-joining. Sekuen koding (coding sequence, cds) parsial 654 bp dari CO1 dan cds parsial 380 bp dari gen 18S rDNA) telah berhasil diamplifikasi dari DNA genom. Sekuensing CO1 menghasilkan fragmen yang terdiri dari 25,84% adenin, 20,95% sitosin, 19,11% guanin, dan 34,10% timin, sedangkan 18S rDNA menghasilkan fragmen yang terdiri dari 24,47% adenin, 26,05% sitosin, 28,16% guanin, dan 21,32% timin. Analisis filogenetik berdasarkan gen CO1 menunjukkan bahwa C. boehmei sekelompok dengan C. variabilis (MK190014), C. brachydactyla (MK190011), dan Caridina sp. (MK190012). Analisis filogenetik berdasarkan gen 18S rDNA menunjukkan bahwa C. boehmei identik dengan Caridina sp. Suphan Buri-1 MF622000, C. serratirostris KP725708, C. multidentata JF346236, C. formosae GQ131924, and Caridina sp. Suphan Buri-2 MF622001. Jarak berpasangan terendah hingga tertinggi berdasarkan CO1 dan 18S rDNA berturut-turut adalah 0,0017-0,2247 (0,17-22,47%) dan 0,0000-0,1218 (0-12,18%). Kata kunci: 18S rDNA, Caridina boehmei, CO1, DNA barcode, udang hias